Особенности обучения взрослых - Караченцева, Е. А. (ХНУРЕ, 2019)
This work is devoted to a review of adult learning methods, namely the development of an adult's ability to self-study and comprehend the new. To date, the world is constructed so that it is necessary to constantly reinforce knowledge to improve the level and quality of life. However, the presence of a decent education in a particular area is insufficient, due to the world is moving over time and it is necessary to acquire new skills in a particular area. There is a theory that describes the features of adult education - andragogy.